2002
DOI: 10.2131/jts.27.57
|View full text |Cite
|
Sign up to set email alerts
|

Prevention by natural food anthocyanins, purple sweet potato color and red cabbage color, of 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP)-associated colorectal carcinogenesis in rats initiated with 1,2-dimethylhydrazine.

Abstract: -The potential of purple sweet potato color (PSPC) and red cabbage color (RCC), natural anthocyanin food colors, to modify colorectal carcinogenesis was investigated in male F344/DuCrj rats, initially treated with 1,2-dimethylhydrazine (DMH) and receiving 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP) in the diet. After DMH initiation, PSPC and RCC were given at a dietary level of 5.0% in combination with 0.02% PhIP until week 36. No PSPC or RCC-treatment-related changes in clinical signs and body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 36 publications
(54 reference statements)
2
58
0
4
Order By: Relevance
“…The minced meat was supplemented with 0.5% sugar, 0.6% pepper, 0.14% allspice, 0.14% coriander, 0.04% cardamom, 0.05% onion powder, 0.05% garlic powder, 0.1% glutamine acid, 0.1% sodium ascorbate, 0.1% sodium polyphosphate N2 (75% sodium polyphosphate, ported that anthocyanins have remarkable antioxidant and free radical scavenging activities (Wang et al, 1997;Tsuda et al, 2000), and can inhibit LDL oxidation in vitro (Käh-könen and Heinonen, 2003). Thus, anthocyanin rich berries, grapes and purple sweet potato may provide possible health benefits, such as reduction of coronary heart disease (Zern et al, 2005), anti-inflammatory activity (Afaq et al, 2005) and anti-cancer activity (Hagiwara et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The minced meat was supplemented with 0.5% sugar, 0.6% pepper, 0.14% allspice, 0.14% coriander, 0.04% cardamom, 0.05% onion powder, 0.05% garlic powder, 0.1% glutamine acid, 0.1% sodium ascorbate, 0.1% sodium polyphosphate N2 (75% sodium polyphosphate, ported that anthocyanins have remarkable antioxidant and free radical scavenging activities (Wang et al, 1997;Tsuda et al, 2000), and can inhibit LDL oxidation in vitro (Käh-könen and Heinonen, 2003). Thus, anthocyanin rich berries, grapes and purple sweet potato may provide possible health benefits, such as reduction of coronary heart disease (Zern et al, 2005), anti-inflammatory activity (Afaq et al, 2005) and anti-cancer activity (Hagiwara et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins are the putative cancer chemopreventive ingredients of bilberry, as borne out by their efficacy in preclinical models, especially those of gastrointestinal malignancies: anthocyanins and anthocyanin-rich fruit extracts decreased aberrant crypt foci and reduced colonic adenocarcinoma burden in rats that had received the chemical carcinogens azoxymethane, 1,2-dimethylhydrazine or 2-amino-1-methyl-6-phenylimidazo [4, 5-b]pyridine (3)(4)(5). Anthocyanin-rich berry extracts protected against esophageal cancer in rodents (6) and reduced adenoma development in Apc Min mice (7), a model of human familial adenomatous polyposis coli.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary phytochemicals exemplified by anthocyanins, bright blue-or red-colored polyphenols, which occur ubiquitously in vegetables and fruits, are attractive candidates for clinical evaluation, as they possess a good safety record. Studies in preclinical carcinogenesis models suggest that anthocyanins may prevent malignancies, notably in the gastrointestinal tract (3)(4)(5)(6)(7)(8). However, many aspects of their clinical pharmacology, such as concentrations achievable in organs targeted for prevention of malignancy, are only poorly understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have also reported anticarcinogenic properties of anthocyanins. In induced rat colon cancer cell models they significantly decreased total tumors as well as aberrant crypts (Hagiwara et al, 2001;Hagiwara et al, 2002;Harris et al, 2001;Lala et al, 2006;Magnusson et al, 2003). Cai and colleagues demonstrated that Red grape pomace extract (oenocyanin) interferes with adenoma development in the Apc Min mouse by affecting tumor burden more prominently than tumor number.…”
Section: Cytotoxicity In Colon and Other Cancer Cell Linesmentioning
confidence: 99%